Training and education program as a major determinant of quality improvement in Malaysian electrical and electronics industry - Abdullah, Muhammad Madi; Uli, Jegak; Ismail, Azman (ProQuest, 2009)
Organizations that are committed to quality improvement invest heavily in training and education (T&Ed) program of their employees. T&Ed program is therefore becomes an important aspect in the human resource management. The aim of the paper is to examine the influence of training and education program on quality improvement in 255 Electrical and Electronics (E&E) firms in Malaysia. The findings reveal that quality improvement in the Malaysian electrical and electronics industries are significantly influenced by training and education. Thus, this study has empirically shown that quality improvement will increase when the firms implement more training and educational programs.